PREDICTORS OF AND BARRIERS ASSOCIATED WITH HEALTH SERVICES UTILIZATION AMONG PERSONS WITH DISABILITY (Proceedings of the International Conference on Public Health, 2019)
In the Philippines, despite numerous initiatives and programs that aims to increase awareness of persons with disability about the different health care benefits intended for them, majority of them still experiences obstacles particularly in accessing health care services. The purpose of the study was to identify predictors and barriers associated to health services utilization among persons with disability. The study used descriptive design, with 77 persons with disability from 3 hospitals in the province of Cavite as respondents. Regression was used to identify the predictors for both health services utilization and barriers. The researcher found out that gender and type of disability has significant differences in terms of health care services utilization, and in terms of experienced barriers, only educational background has significant difference. Further, the study also revealed that age, location and monthly income were significant predictor in utilization of health care services. While, education became significant predictor in predicting barriers in accessing health care services. Different barriers were identified in low level health care services utilization among persons with disability. In this context, strong implementation of policy to increase awareness and knowledge about disability and its prevention in the community level are essential to address the barriers.
Keywords: Persons with Disability; Health utilization; Health barriers; Health Systems